Double-layer microneedle patch as well as preparation method and application thereof

Through the double-layer microneedle patch, the combination of GCM-MN microneedle array and CSH hydrogel patch is used to solve the problem that drugs can hardly reach the depths of the wound, and effective control of wound infection and promotion of wound healing is achieved.

CN119565014AActive Publication Date: 2025-03-07THE PEOPLES HOSPITAL OF GUANGXI ZHUANG AUTONOMOUS REGION

Patent Information

Application Number
CN202411721588.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-07
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The prior art is difficult to make drugs reach deep into the wound, and it is difficult to effectively control wound infection and promote wound healing.

Method used

A double-layer microneedle patch is used, including a drug delivery unit GCM-MN microneedle array and an adhesion unit CSH hydrogel patch. The GCM-MN microneedle array loads GCM nanoparticles through γ-PGA as the needle tip matrix material, and combines PVP as the backing layer material to ensure the penetration and biocompatibility of the microneedle. CSH hydrogel patches provide a moist healing environment and good adhesion.

Benefits of technology

Deep penetration and effective release of drugs are achieved, significantly reducing wound infection, promoting wound healing, and promoting epithelial regeneration and neovascularization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565014A_ABST
    Figure CN119565014A_ABST
Patent Text Reader

Abstract

The invention relates to a double-layer microneedle patch and a preparation method and application thereof.The double-layer microneedle patch comprises a drug delivery unit and an adhesion unit, the drug delivery unit is a GCM-MN microneedle array, the adhesion unit is a CSH hydrogel patch, and when the double-layer microneedle patch is used, firstly, the GCM-MN microneedle array acts on a wound through pressure, and then the CSH hydrogel patch covers the GCM-MN microneedle array. The CSH hydrogel patch is beneficial to creating a wet healing environment, has excellent adhesion stability and skin adaptability and provides an adhesion barrier for a wound, and the GCM-MN microneedle array has good cell compatibility, cell affinity, blood compatibility and biodegradability. Along with the degradation of the microneedle array at the wound, the packaged GCM nanoparticles are continuously released and go deep into the wound. Therefore, the double-layer microneedle patch disclosed by the invention has huge clinical application potential in the field of infectious wound treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical technology, and in particular to a double-layer microneedle patch and a preparation method and application thereof. Background Art

[0002] Skin tissue is susceptible to various external factors (such as trauma, surgery, and burns) or internal factors (such as diabetes and vascular diseases), which lead to the destruction of its anatomical continuity, thereby damaging the skin barrier and making it easy for bacteria to enter deeper tissues. Bacterial infection of open wounds significantly delays wound healing and inhibits angiogenesis by prolonging the inflammatory period and causing cell damage. It can be seen that bacterial colonization at the wound site poses a major challenge to wound healing. Therefore, the development of strategies that can effectively control wound infection and accelerate wound healing has become a key task in the biomedical field.

[0003] In recent years, metal ions, metal oxides and metal hydroxides (such as silver, zinc, copper, cobalt, cerium and gallium) have been used as alternatives or supplements to antibiotics for infection prevention and control. MOFs are a class of porous hybrid coordination polymers formed by self-assembly of metal ions and organic ligands. Compared with traditional metals and metal oxides, MOFs are more gentle as a reservoir of metal ions. In addition, the structural characteristics of MOFs organic ligands are also important determinants of their antibacterial activity. In addition, the pore structure of MOFs is often considered to be its most significant and valuable feature, providing elastic pores superior to molecular sieves and higher loading capacity than lipids or polymers. For example, the Chinese invention patent with application number CN202411099352.7 (publication number CN118873734A) is entitled "A Cu-MOF-based composite antibacterial hydrogel wound dressing and its preparation method", and the Chinese invention patent with application number CN202410217827.1 (publication number CN118079075A) is entitled "A nanoreactor hydrogel for promoting diabetic wound healing and its preparation method and application". Furthermore, metformin (Met) is a natural product extracted from the leguminous plant Galega officinalis, which is often used as an oral hypoglycemic drug for the treatment of type 2 diabetes. Recent studies have shown that metformin also has anti-inflammatory effects and regulates the proliferation, migration and angiogenesis of vascular cells such as endothelial cells by activating the AMPK pathway.

[0004] However, the therapeutic efficacy of multifunctional MOF platforms is often limited by their tissue penetration, which is usually limited to the epidermis of the wound, and for deeper wounds, successfully regenerating the dermis is more challenging than restoring the epidermis. This is because the repair of infected wounds requires not only restoring the epidermis, but also removing bacteria in the dermis and fully regenerating skin appendages (e.g., cysts, glands, and blood vessels). Summary of the invention

[0005] The first technical problem to be solved by the present invention is to provide a double-layer microneedle patch that enables drugs to directly reach deep into the wound in response to the existing technology.

[0006] The second technical problem to be solved by the present invention is to provide a double-layer microneedle patch with good applicability, which can enable drugs to directly reach deep into the wound, in view of the existing technology.

[0007] The third technical problem to be solved by the present invention is to provide a double-layer microneedle patch that can effectively control wound infection in view of the existing technology.

[0008] The fourth technical problem to be solved by the present invention is to provide a double-layer microneedle patch that can effectively control wound infection and promote wound healing in view of the existing technology.

[0009] The fifth technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned double-layer microneedle patch in view of the prior art.

[0010] The sixth technical problem to be solved by the present invention is to provide an application of the above-mentioned double-layer microneedle patch in view of the prior art.

[0011] The technical solution adopted by the present invention to solve at least one of the above technical problems is: a double-layer microneedle patch, characterized in that it includes a drug delivery unit and an adhesion unit, wherein the drug delivery unit is a GCM-MN microneedle array, and the adhesion unit is a CSH hydrogel patch, and when in use, the GCM-MN microneedle array is first applied to the wound by pressure to ensure that the microneedles can penetrate the skin of the wound, and then the CSH hydrogel patch is covered on the GCM-MN microneedle array to ensure a moist healing environment.

[0012] Furthermore, the GCM-MN microneedle array uses γ-PGA as the matrix material of the needle tip to load the GCM nanoparticles, and uses PVP as the backing layer material, and PVP has good biosafety, mechanical strength and rapid solubility. In the present invention, γ-polyglutamic acid (γ-PGA) and PVP are biocompatible macromolecules with good biodegradability and hygroscopicity. These properties enable GCM-MN to absorb skin interstitial fluid and degrade, thereby promoting the release of GCM nanoparticles.

[0013] Furthermore, the needle tips of the GCM-MN microneedle array are all pyramid-shaped, and the length of each needle tip is 640 μm, the base diameter is 320 μm, and the distance between adjacent needle tips is 550 μm. The thickness of the avascular epidermis of the outermost layer of the skin is about 100 μm, while the thickness of the vascular-rich dermis below is usually between 1000 and 2000 μm. Therefore, the 640 μm long GCM-MN in the present invention is sufficient to penetrate the epidermis and reach the dermis, which is conducive to the delivery of drugs.

[0014] The technical solution adopted to further solve the fifth technical problem is: a method for preparing a double-layer microneedle patch as described above, characterized in that it includes the following steps: (1) synthesis of GCM; (2) preparation of a GCM-MN microneedle array; (3) preparation of a CSH hydrogel patch.

[0015] Further, the synthesis steps of GCM in step (1) are as follows: Ga(NO3)3 and Met are mixed in water to react and produce Ga 3+ and Met coordination complex; subsequently, carbenicillin solution was added to 3+ A Ga-Car-MOF complex is formed; after stirring the reaction, the precipitate is collected and washed to remove unreacted substances; finally, white GCM nanoparticles are obtained after freeze-drying.

[0016] Furthermore, the preparation steps of the GCM-MN microneedle array in step (2) are as follows: a two-step template replication method is used. First, the GCM nanoparticles prepared in step (1) are dispersed in water and mixed with γ-PGA, and the mixture is obtained by vacuum and low-speed centrifugation; then, the mixture is filled into the needle tip of the needle mold, and after removing excess material, pure PVP pregel is added to form a GCM-MN microneedle array.

[0017] Furthermore, the preparation steps of the CSH hydrogel patch in step (3) are as follows: first, chitosan is modified by covalently bonding hydrogenated caffeic acid to form CSH; then, the CSH solution is cross-linked in a mold to prepare a CSH hydrogel patch.

[0018] The technical solution adopted to further solve the sixth technical problem mentioned above is: application of the double-layer microneedle patch in the preparation of infectious wound healing medical devices.

[0019] Compared with the prior art, the advantages of the present invention are: the double-layer microneedle patch (GCM-MN-CSH) of the present invention includes a drug delivery unit and an adhesion unit, wherein the drug delivery unit is a GCM-MN microneedle array, and the adhesion unit is a CSH hydrogel patch. When the double-layer microneedle patch is applied to bacterial infection wounds, the CSH hydrogel patch is conducive to creating a moist healing environment, showing seamless skin adhesion, having excellent adhesion stability and skin adaptability, and providing an adhesion barrier for the wound. At the same time, the GCM-MN microneedle array of the present invention has good cell compatibility, cell affinity, blood compatibility and biodegradability. Moreover, as the microneedle array degrades at the wound site, the encapsulated GCM nanoparticles are continuously released and penetrate into the wound site.

[0020] Specifically, the positively charged surface of GCM nanoparticles (where the amino groups in the Met molecules increase the positive charge of GCM) enhances its adsorption to bacteria, increasing contact and promoting lysis through acidic reactions, Ga 3+ The synergistic effect of metformin and carbenicillin enhances the antibacterial activity. Metformin further enhances the proliferation, migration, angiogenesis and collagen deposition of endothelial cells, while increasing the infiltration of M2 macrophages in tissues. The double-layer microneedle patch of the present invention has been verified by experiments to have a strong antibacterial effect (including in vivo and in vitro antibacterial), can effectively reduce inflammatory response, activate protective immune response, and promote epithelial regeneration and the formation of new blood vessels.

[0021] The above effects jointly promote infection control, reduce inflammation, stimulate tissue proliferation and promote tissue remodeling, ultimately supporting programmed wound healing and accelerating wound healing. It can be seen that the double-layer microneedle patch (GCM-MN-CSH) of the present invention has great clinical application potential in the field of infectious wound treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1Synthesis and characterization of GCM nanoparticles: (A) Schematic diagram of the one-pot synthesis process of GCM nanoparticles; (B) FE-SEM image of GCM nanoparticles; (C) FE-SEM image of GC nanoparticles; (D) Particle size distribution of GC and GCM nanoparticles; (E) FTIR spectra of Met, Car, GC and GCM; (F) XRD patterns of GC and GCM; (G) In vitro release curves of carbenicillin (Car) from GCM nanoparticles in PBS solutions of 5.5 and 7.4; (HI) Effects of different concentrations of GCM nanoparticles on the survival rates of Staphylococcus aureus (S. aureus) (H) and Pseudomonas aeruginosa (P. aeruginosa) (I) under different pH conditions; (J) Dynamic light scattering (DLS) was used to measure the surface ζ potential of GC (I), GCM (II), S. aureus (III), S. aureus co-cultured with GC (IV), S. aureus co-cultured with GCM (V), P. aeruginosa (VI), P. aeruginosa co-cultured with GC (VII), and P. aeruginosa co-cultured with GCM (VIII); (K) SEM images of S. aureus and P. aeruginosa samples after treatment with GC nanoparticles and GCM nanoparticles;

[0023] Figure 2 Synthesis and characterization of GCM-MN-CSH: (A) Optical image of GCM-MN-CSH patch; (B) Schematic diagram of the preparation process of double-layer GCM-MN-CSH patch; (C) Field emission scanning electron microscopy (FE-SEM) image of GCM-MN, scale bar: 300 μm; (D) Local magnified FE-SEM image of GCM-MN, scale bar: 100 μm; (E) Fluorescence microscopy image of the GCM-MN tip labeled with rhodamine B, scale bar: 50 μm; (F ) Photographs of GCM-MN applied to pig skin and stained with 0.4% trypan blue; (G) Morphological images under a microscope showing the moisture absorption of GCM-MN at different time points in a 100% humidity chamber at room temperature, scale bar: 200 μm; (H) In vitro release curves of GCM-MN in PBS at pH 5.5 and 7.4; (I) Optical images of CSH applied to joints and skin and still able to adhere to the skin when subjected to a 3 g weight; (J) Comparison of the adhesion strength of CSH and GCM-MN-CSH;

[0024] Figure 3The in vitro antibacterial ability of GCM-MN: (A) Bacterial activity of Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) after treatment with different treatment groups; (B) Statistical bar graph showing the colony counts of Staphylococcus aureus and Pseudomonas aeruginosa after different combination treatments; (C) Standard plate images of Staphylococcus aureus and Pseudomonas aeruginosa under different treatment groups; (D) Fluorescence images of Staphylococcus aureus and Pseudomonas aeruginosa stained with SYTO 9 / PI under a fluorescence microscope after different treatment groups, scale bar: 50 μm;

[0025] Figure 4 Evaluation of the biocompatibility and angiogenic ability of GCM nanoparticles (NPs) and GCM-MNs in vitro: (A) Cell viability of HUVEC cells exposed to different concentrations of GCM nanoparticles and GCM-MNs for 24 hours; (B) Hemolysis rate of different concentrations of GCM nanoparticles; (C) Hemolysis rate of different concentrations of GCM-MNs; (D) Microscope images of HUVECs treated with GCM nanoparticles and GCM-MNs, showing cell migration at 0 hours and 12 hours, scale bar: 200 μm; (E) Representative quantitative analysis of migration rate; (F) Microscope images of HUVECs undergoing endothelial tube formation experiment, scale bar: 200 μm; (G) Representative quantitative analysis of the total tube length of each group; (H) Representative quantitative analysis of the number of nodes in each group;

[0026] Figure 5 GCM-MN-CSH promotes healing of infected wounds in vivo: (A) Schematic diagram of the in vivo treatment of infected wound models by GCM-MN-CSH; (BD) Dynamic changes of wound healing in different treatment groups: sequential photos (B), wound bed closure trajectory (C), statistical analysis of wound area (D), observed on days 0, 2, 4, 6 and 8, including control group (I), blank microneedle (blank-MN) (II), Met-MN (III), GC-MN (IV), GCM-MN (V) and GCM-MN-CSH (VI) groups; (EF) Photos (E) and quantitative analysis (F) of residual bacteria on LB medium plates at the wound site on day 8 after treatment; (G) Weight change rate of mice in different treatment groups during wound healing;

[0027] Figure 6To study wound tissue regeneration, angiogenesis and immunofluorescence staining after treatment: (A) H&E staining, Masson's trichrome staining and immunofluorescence staining images of wounds in different groups on day 8: control group (I), blank-MN group (II), Met-MN group (III), GC-MN group (IV), GCM-MN group (V), GCM-MN-CSH group (VI) (B) Representative quantitative analysis of wound epidermal thickness; (C) Representative quantitative analysis of relative collagen deposition levels; (DE) Representative quantitative analysis of relative fluorescence intensity: IL-1β (D) and IL-6 (E). (FG) Representative quantitative analysis of mean fluorescence intensity of CD 86 (F) and CD 206 (G); (HI) Representative quantitative analysis of mean fluorescence intensity of α-SMA (H) and CD 31 (I);

[0028] Figure 7 High-performance liquid chromatography (HPLC) analysis of the loading amount of Met in GCM: (A) Standard curve of Met concentration and peak area at 233 nm determined by HPLC with UV detection; (B) Loading rate of Met in GCM nanoparticles;

[0029] Figure 8 The antibacterial effect of GCM: (A) the activity of Staphylococcus aureus (S. aureus) after treatment with GCM nanoparticles at different concentrations and time points; (B) the activity of Pseudomonas aeruginosa (P. aeruginosa) after treatment with GCM nanoparticles at different concentrations and time points;

[0030] Fig. 9 Results of bacterial activity inhibition: (A) Bacterial activity; (B) Quantitative analysis using the standard plate counting method; (C) Standard plate images of Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) after treatment with different components;

[0031] Fig.10 Fluorescence microscopy images of Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) stained with SYTO9 / PI after treatment with different components, scale bar: 50 μm;

[0032] Fig.11 Verification of the formation and degree of covalent bonds in CSH: (A) UV–vis absorption spectra of salicylic acid and CSH; (B) FTIR spectra of CS, salicylic acid, and CSH; (C) The connection efficiency of salicylic acid in CSH;

[0033] Fig.12 This is an optical photograph of GCM-MN;

[0034] Fig.13Optical images and adhesion of CSH hydrogel patches: (A) Optical image of CSH hydrogel patches; (B) Adhesion of CSH hydrogel to skin;

[0035] Fig.14 EDS element mapping of C, N, O, S and Ga elements in the GCM-MN array, scale: 100 μm;

[0036] Fig.15 Typical force-displacement curves during compression of a single tip in blank-MN and GCM-MN arrays;

[0037] Fig.16 This is the dissolution process of GCM-MN after being inserted into the wound skin of mice;

[0038] Fig.17 Cell viability of NIH / 3T3 cells after treatment with different concentrations of GCM nanoparticles (GCM NPs) and GCM-MNs for 24 h;

[0039] Fig.18 Effects of GCM nanoparticles (GCM NPs) and GCM-MNs on NIH-3T3 cell migration: (A) Representative images of scratch wound migration, scale bar: 200 μm; (B) Quantitative analysis of NIH-3T3 cell migration rate after 24 hours;

[0040] Fig.19 HE staining shows the effect of GCM-MN-CSH on the main organs of mice. DETAILED DESCRIPTION

[0041] Example 1: Experimental Materials and Methods

[0042] 1.1. Materials and chemicals

[0043] Gallium nitrate (Ga(NO3)3), carbenicillin (Car), and high molecular weight γ-polyglutamic acid (γ-PGA, Mw>700,000) were purchased from Aladdin Biochemical Technology Co., Ltd. (Shanghai, China); metformin (Met) and hydrocaffeic acid (Hydrocaffeic acid) were purchased from Adamas-Beta (Shanghai, China); chitosan (CS, 200 kDa, deacetylation degree>95%) was purchased from MacLean Biochemical Co., Ltd. (Shanghai, China); and rhodamine B was purchased from Bede Pharmaceutical Co., Ltd. (Shanghai, China).

[0044] The cell counting kit (CCK-8) was purchased from Thermo Fisher Scientific (Pittsburgh, USA); tryptone soy broth (TSB), Luria-Bertani (LB) medium and agar premix powder, and Live / Dead BacLight bacterial viability kit (L7012) were purchased from Solarbio Science and Technology (Beijing, China).

[0045] High-glucose Dulbecco's modified medium (HG-DMEM) and fetal bovine serum (FBS) were purchased from Israel Bioindustry; growth factor-reduced (GFR) Matrigel was purchased from Corning Incorporated (New York, USA).

[0046] 1.2. Synthesis of GCM and GC

[0047] GCM was synthesized by the existing single-pot stirring method, and the specific steps are as follows:

[0048] 10 mmol of Ga(NO3)3 and Met were mixed in 12 mL of water, followed by slow dropwise addition of 6 mL of a solution containing 5 mmol of carbenicillin (Car). The mixture was stirred at room temperature for 48 hours, and then separated by centrifugation (12,000 × g) to obtain a white precipitate, which was washed three times with deionized water to remove unreacted chemicals and freeze-dried at -60 ° C for 12 hours. The synthesis process of GC was similar to the above steps, except that Met was not added.

[0049] To quantify Met in GCM, the supernatant after synthesis was collected, filtered through a 0.22 μm membrane, and analyzed by high performance liquid chromatography (HPLC, Thermo Fisher UltiMate 3000, USA). A Hypersil GOLD-C18 column (250 × 4.6 mm, 5 μm) and a Vanquish variable wavelength detector were used. The sample (20 μL) was eluted with a mixture of 10 mM sodium dihydrogen phosphate (pH 3.5) and methanol in a ratio of 85:15 (v / v) at a flow rate of 1 mL / min, and the detection wavelength was 233 nm. The Met concentration was quantified using a standard curve (R 2 =0.999), and the concentration range is 0.03125mg / mL~0.5mg / mL.

[0050] 1.3. Characterization of GCM

[0051] The morphology of GCM and GC particles was observed using a field emission scanning electron microscope (FE-SEM) (Carl Zeiss, Oberkochen, Germany) at 5 kV, and the particle size was measured using ImageJ software. Fourier transform infrared spectroscopy (FTIR) was performed using a Nicolet iS10 FTIR spectrometer (Thermo Fisher Scientific, Massachusetts, USA) at 2 cm -1The structural characterization was performed by Bruker D8 X-ray diffractometer (copper target) scanning from 5° to 40° 2θ at a speed of 2° / min. The zeta potential was determined by Malvern Zetasizer Nano ZS90 (Malvern Instruments Ltd, Worcestershire, UK).

[0052] To evaluate the release of carbenicillin (Car) and metformin (Met) from GCM nanocomplexes, 12 mg of GCM was dispersed in 12 mL of 0.05 M PBS at pH 5.5 and 7.4, respectively, and maintained at room temperature. 300 μL of supernatant samples were collected at regular intervals (0, 1, 3, 6, 9, 12, 24, and 48 hours). For Car, 20 μL of sample was analyzed under isocratic conditions using a 65:35 mixture of 0.05 M KH2PO4 (pH 3.35) and methanol at a flow rate of 1 mL / min. The Car concentration was quantified using two standard curves, which were the concentration-peak area relationship (R) at pH 5.5 and pH 7.4, respectively. 2 =0.999). The concentration range of these curves is 15.625 μg / mL to 500 μg / mL.

[0053] 1.4. Formation and characterization of CSH hydrogel patches

[0054] First, chitosan was modified by covalently binding chitosan to ammonium salicylate, as follows: chitosan at a concentration of 0.058 mol / L was dissolved in 21.25 mL of water at pH 1.6. Then, the pH was adjusted to 5.4 with 1 M NaOH, and 1.5 mL of 1.08 mol / L ammonium salicylate solution was added. Next, 0.6224 g of EDC-HCl (dissolved in 25 mL of 50% ethanol solution) was gradually added, and the pH was adjusted to 4.6 with 1 M NaOH, and the reaction was stirred at room temperature for 12 hours. After the reaction, the reaction solution was dialyzed using a dialysis bag with a molecular weight cutoff of 14,000 Da, first in pure water at pH 5.0 for 2 days, then in pure water at pH 5.5 for 4 hours, and the dialysate was replaced every 3-6 hours. After dialysis, CSH was obtained by freeze-drying.

[0055] To prepare the hydrogel patch, 67.5 mg of CSH was dissolved in 1.5 mL of PBS. The solution was centrifuged at 3,000 rpm for 5 minutes to remove air bubbles, then transferred to a 2 cm × 2 cm mold and dried in a desiccator for 6 hours.

[0056] Synthesis verification: The UV-visible absorption spectra of ammonium hydrogen salicylate and CSH were recorded by visible spectroscopy, and their chemical structures and functional groups were characterized by FTIR spectrometer.

[0057] Adhesion performance verification: The adhesion performance of the hydrogel patch was evaluated by applying it to human skin and observing whether it fell off. In addition, an EP tube filled with water (about 3 grams) was attached to the hydrogel to evaluate its adhesion strength.

[0058] 1.5. Preparation of GCM-MN Arrays

[0059] 10 mg / mL of GCM powder was dispersed in 0.9 mL of γ-PGA (390 mg / mL) solution and loaded into a PDMS mold. The solution was distributed into the pinholes by vacuum degassing for 2 minutes and horizontal centrifugation (3,000 rpm) for 5 minutes. Then, 300 μL of 20% polyvinyl pyrrolidone (PVP) solution was added to form the backing layer of the array. After drying for 9 hours, the molds were carefully demolded and stored for subsequent use and analysis. Control MNs were prepared by the same method and contained Met, Ga and Car equivalent to GCM and GC at the same concentration as GCM.

[0060] Characterization of GCM-MN-CSH

[0061] Microstructure characterization: The microstructure of GCM-MN was analyzed by Hitachi SU8010 FE-SEM (enhanced metallization coating), and the element distribution was determined by EDX-assisted SEM (energy dispersive X-ray analysis).

[0062] Distribution of GCM in MNs: The distribution images of GCM nanoparticles labeled with rhodamine B in GCM-MNs were captured using a Nexcope NIB620-FL fluorescence microscope.

[0063] Mechanical strength: To evaluate skin insertion ability, GCM-MN arrays labeled with 0.4% trypan blue were applied to fresh porcine skin, removed after 1 min, and the micropores on the skin were examined using a digital microscope. In addition, a mechanical tensile tester (AMETEK Inc, Leicester, UK) was used to evaluate the mechanical integrity of the GCM-MNs. The MNs were compressed at a speed of 0.5 mm / min on a horizontal sample stage. Force-displacement curves were then plotted to evaluate the results.

[0064] Solubility test: GCM-MNs were exposed to 100% relative humidity in sealed bottles, and the changes in morphology at different time points (0, 15, 30, 45, 60, and 75 minutes) were recorded using an optical microscope. For in vivo solubility testing, GCM-MNs were applied to the skin of anesthetized mice, allowed to penetrate, and photographed at different time points (0, 5, 10, 15, 20, 25, 30 minutes) to observe the dissolution of the microneedles.

[0065] Adhesion test: Freshly dried pigskin was fixed on the base of a mechanical testing machine, and the CSH patch was adhered to both sides of the pigskin and stretched until separation occurred. The maximum force at the moment of separation was recorded to calculate the adhesion stress. For the GCM-MN-CSH sample, the GCM-MN was first inserted into the pigskin, and then the CSH patch was attached.

[0066] GCM release curve measurement: Single GCM-MNs were immersed in 3 mL of PBS at pH 5.5 and 7.4, respectively. The absorbance of the supernatant was measured at 250 nm using a UV-2700 spectrometer (Shimadzu Corporation, Kyoto, Japan) every 10, 20, 30, 60, 120, and 180 minutes. The concentration of GCM was quantified by constructing a standard curve using GCM PBS solutions with known concentrations.

[0067] 1.7. Antimicrobial test

[0068] 1.7.1. Bacterial culture preparation

[0069] Gram-positive Staphylococcus aureus (S. aureus, ATCC 29213) and Gram-negative Pseudomonas aeruginosa (P. aeruginosa, ATCC 27853) were cultured in TSB and LB medium, respectively, at 37°C for 12 h. After culture, the bacterial suspension was centrifuged at 10,000 × g for 1 min at 4°C, washed three times with PBS to remove residual medium, and then resuspended in PBS to obtain the required concentration for the experiment.

[0070] Evaluation of antibacterial activity of GCM nanoparticles

[0071] Different concentrations of GCM nanoparticles (0, 10, 30, 50, 70 μg / mL) were mixed with 1×10 6 CFU / mL of bacteria were mixed in PBS / medium at pH 5.5 and 7.4, respectively. Culture was carried out at 37°C in 96-well plates. Bacterial proliferation was evaluated by CCK-8 method and counted after 1, 2, 3, 4, and 5 hours of culture. In addition, colony counting method was performed. Control concentrations included 16.97μg / mL of Met, 30.25μg / mL of Car, 2.78μg / mL of Ga, and 50μg / mL of GC. SEM was used to analyze bacterial morphology before and after GCM and GC treatment. The zeta potential of GCM and GC mixed with bacteria was measured by Malvern Zetasizer Nano ZS90.

[0072] Antimicrobial activity of MN

[0073] MNs of different compositions (blank-MN, Met-MN, Car-MN, Ga-MN, GC-MN and GCM-MN) were mixed with 1×10 6 CFU / mL of bacterial solution was co-cultured at pH 5.5. Incubated in microplates at 37°C for 3 hours, bacterial proliferation was assessed using the CCK-8 method, and the killing rate was quantified by colony counting. SYTO 9 (live cells) and PI (dead cells) staining were used to assess bacterial activity.

[0074] 1.8. In vitro cell experiments

[0075] 1.8.1. Cell proliferation assessment

[0076] Mouse embryonic fibroblasts (NIH / 3T3) and human umbilical vein endothelial cells (HUVECs) were used to evaluate the cytotoxicity of GCM nanoparticles and GCM-MNs, respectively. Both cell types were cultured in high glucose DMEM medium supplemented with 10% fetal bovine serum at 37°C in a 5% CO2 atmosphere. Cells were seeded in 96-well plates at 1×10 4 cells. GCM nanoparticles and GCM-MNs were sterilized by UV light for 15 minutes and then placed on the cell layer. After incubation for 24 hours, CCK-8 reagent was added and incubated for another 2 hours. The absorbance was measured at 450 nm by a microplate reader to calculate the cell viability.

[0077] Cell migration assay

[0078] In vitro wound healing assay was used to evaluate the chemotactic effect of GCM and GCM-MN on the migration of HUVECs and NIH / 3T3 cells. The cells were seeded in 6-well plates at a seeding density of 1×10 6 , cultured to about 90% confluence. A scratch was created in the cell monolayer using a sterile pipette tip. GCM and GCM-MN were irradiated with ultraviolet light for 15 minutes and then added to the culture medium at a concentration of 50 μg / mL. 2 mL of DMEM containing 2% fetal bovine serum was used as a control. The control group, GCM group, and GCM-MN group were incubated with cells for 12 hours and 24 hours. After incubation, cell migration was observed using bright field microscopy and the scratch gap was measured. ImageJ software was used to quantify the scratch closure, and the migration rate was calculated as follows: migration rate = (initial scratch area - final scratch area) / initial scratch area.

[0079] 1.8.3. Lumen formation analysis

[0080] The in vitro tube formation assay was used to evaluate the angiogenic effects of GCM and GCM-MN on HUVECs. Each well of a 48-well plate was coated with 150 μL of growth factor-reduced matrix gel, refrigerated overnight, and then incubated at 37°C for 30 minutes to form a gel. 5 HUVECs were seeded on the solidified gel and treated with serum-free DMEM containing 50 μg / mL GCM and GCM-MN, or left untreated as a control group. After incubation for 6 hours, cell images were taken using a bright field microscope. The number of branch points and average tube length were quantified using ImageJ software to analyze tube lumen formation.

[0081] 1.9. In vivo wound healing assessment

[0082] 1.9.1. Rat full-thickness infected wound model

[0083] The infection trauma model was established in BALB / c female mice (13-15 g, 5 weeks old). The mice were first intraperitoneally injected with 0.2 mL / 10 g of 1.25% bromoethanol solution, followed by shaving, disinfection with medical alcohol and iodine, and a circular incision was made at the back wound site using a 6 mm diameter biopsy puncture knife. The wound was inoculated with 20 μL of Staphylococcus aureus (S. aureus) suspension (1×10 7 CFU / mL). After 24 hours, the mice were randomly divided into six groups: PBS (control group), blank-MN, Met-MN, GC-MN, GCM-MN and GCM-MN-CSH. The MN array was applied under anesthesia and replaced every day for the first four days. The mice were housed under standard conditions, ensuring sufficient food and water. The progress of wound healing was recorded by taking pictures, and the wound area was quantified on days 0, 2, 4, 6 and 8, and analyzed using Image-Pro Plus software. The wound area rate was calculated as follows: wound area rate = (wound area / initial wound area) × 100%. On the 8th day after treatment, wound tissue was collected and bacterial clearance was evaluated using the standard plate count method. 1.9.2. Histology and immunohistochemical staining

[0084] After 8 days of treatment, all mice were euthanized and skin tissues containing the wound area were collected. The tissues were fixed with 4% paraformaldehyde for 24 hours, embedded in paraffin, and sliced ​​into 5 μm slices for histological examination. Granulation tissue formation and collagen deposition were evaluated by HE (Hematoxylin-Eosin) staining and Masson's trichrome staining. Immunohistochemical staining was used to evaluate inflammation and immune response, using IL-1β (inflammation), IL-6 (inflammation), CD206 (M2 macrophages), and CD86 (M1 macrophages) markers. New angiogenesis was analyzed by CD31 (endothelial cell marker) and α-SMA (fibroblast marker) staining. In addition, major organs (including heart, liver, spleen, lungs, and kidneys) of all groups were collected and HE staining was performed to evaluate systemic effects.

[0085] 1.10. In vitro blood compatibility test

[0086] The hemolysis rate was used to evaluate the blood compatibility of GCM and GCM-MN. Red blood cells were separated from the blood of BALB / c mice (4°C, 15 minutes) by centrifugation and washed with saline until the supernatant was colorless. The red blood cell suspension was diluted to 4% (v / v). Different concentrations of GCM and GCM-MN extracts (6.25, 12.5, 25, 50 and 100 μg / mL) were added to equal volumes of red blood cell suspensions. Physiological saline and ultrapure water were used as negative and positive controls, respectively, and each group was mixed with an equal volume of 2% red blood cell suspension. All groups were incubated at 37°C for 4 hours, centrifuged at 1500×g, and after 5 minutes, the absorbance of 100 μL supernatant was measured at 540 nm. The hemolysis rate calculation formula is:

[0087] Hemolysis rate = (supernatant absorbance - control absorbance) / (positive control absorbance - negative control absorbance) × 100%.

[0088] Statistical analysis

[0089] All data were derived from three or more independent experiments, and the results are expressed as mean ± standard deviation (SD). GraphPad Prism 8 software (GraphPad Software, California, USA) was used for data analysis. The statistical significance between two groups was determined by Student's t-test, while the differences between multiple groups were assessed by one-way analysis of variance (ANOVA). The statistical significance level was set at a p value less than 0.05. Statistically significant results are indicated as follows: *p<0.05, **p<0.01, ***p<0.001, ****p<0.0001, ns indicates no significant difference.

[0090] Example 2: Test results

[0091] Synthesis and characterization of GCM nanoparticles

[0092] GCM nanoparticles were synthesized by an existing one-pot method, the synthesis process is as follows Figure 1 As shown in A. First, Ga(NO3)3 and Met are mixed in water to react and produce Ga 3+ and Met coordination complex. Subsequently, carbenicillin (Car) solution was added and mixed with Ga 3+ The Ga-Car-MOF complex was formed. After 48 hours of stirring reaction, the precipitate was collected and washed with deionized water to remove the unreacted substances. Finally, white GCM nanoparticles were obtained after freeze drying.

[0093] The loading amount of Met in GCM was analyzed by high performance liquid chromatography (HPLC). The results showed that the loading efficiency of Met in GCM was 34.0±2.2% ( Figure 7 The morphology of GCM was observed by scanning electron microscopy (SEM), and the results showed that its particles were spherical with a diameter of about 75.1±12.1nm ( Figure 1 B. Figure 1 D), and the particle size distribution is relatively uniform. In contrast, the average diameter of GC particles is 49.0±7.9nm ( Figure 1 C. Figure 1 D). This difference in particle size may be related to the addition of Met, which has a larger molecule and leads to an increase in the size of GCM particles. Fourier transform infrared spectroscopy (FTIR) analysis further confirmed the successful synthesis of GCM. Figure 1 The FTIR spectrum in E shows that at 1380 cm -1 、2970cm -1 and 1770cm -1 There are significant absorption peaks at 1153 cm-1, corresponding to the C-C stretching vibration of the aromatic ring, the bending vibration of the -C(CH3)2 group, and the C=O stretching vibration of carbenicillin. -1 and 1228cm -1 The absorption peak at is significantly enhanced, indicating that Met has been embedded into the MOF framework, which is consistent with the HPLC data. The X-ray diffraction (XRD) patterns of GCM and GC show characteristic diffraction peaks consistent with the known structure of Ga-Car-MOF ( Figure 1 F). In particular, the diffraction peak at 18.1° indicated that the crystal structure of GCM was preserved. In addition, the zeta potential of GCM particles increased from 8.21±0.40 mV of GC to 11.17±0.42 mV ( Figure 1J), this change indicates that the introduction of Met enhances the positive charge of the particles. The amino group in the Met molecule increases the positive charge of GCM, which may also enhance its interaction with the negatively charged bacterial surface, thereby improving the antibacterial performance. In summary, the characterization methods such as SEM, FTIR and XRD show that the present invention successfully prepared GCM nanoparticles with the expected morphology and structure, and further verified its effective loading of Met in MOF.

[0094] Considering the slightly acidic pH of the wound microenvironment (usually between 5 and 6), and the tendency of wound pH to alkaline with the progression of clinical infection. In addition, previous studies have shown that carbenicillin (Car) and Ga 3+ The coordination bond between is sensitive to low pH. Therefore, the present invention evaluates the concentration of Car released by GCM in PBS solutions at pH 5.5 and 7.4 to study the pH-responsive degradation ability of GCM. The results of the present invention show that after 48 hours, about 392.08±7.82μg / mL of Car was released under pH 5.5 conditions, while only 205.41±26.02μg / mL was released under pH 7.4 conditions ( Figure 1 G). This result indicates that GCM retains the pH-sensitive properties of GC and can efficiently release most of the drug-loaded substances in an acidic environment. Specifically, the release of Car from GCM increases with decreasing pH, while it exhibits a slower and lower release rate under neutral conditions.

[0095] Wounds exposed to the external environment are susceptible to infection by pathogenic bacteria, such as Staphylococcus aureus, Enterococcus, Enterobacteriaceae, and Pseudomonas aeruginosa. These bacteria may cause sepsis and lead to potential life-threatening complications. Therefore, it is crucial to eliminate these bacteria during wound healing. In order to evaluate the antibacterial effect of GCM, the present invention uses CCK-8 method and colony counting method to test its antibacterial and bactericidal effects on Gram-positive Staphylococcus aureus (S. aureus) and Gram-negative Pseudomonas aeruginosa (P. aeruginosa), respectively. Preliminary tests show that when the concentration of GCM exceeds 50 μg / mL, its survival rate is almost reduced to zero after incubation with S. aureus for 1 hour ( Figure 8 A), and the survival rate reached a similar level after 3 hours of co-incubation with P. aeruginosa ( Figure 8 B). Considering the acidic microenvironment of acute trauma, the present invention further studied the antibacterial effect of GCM under pH 5.5 and 7.4. Figure 1As shown in HI, GCM can significantly reduce bacterial survival at pH 5.5 than at pH 7.4, indicating that the antibacterial activity of GCM depends on pH, and the antibacterial effect increases when the pH decreases. It is worth noting that only at pH 5.5, 30μg / mL of GCM can completely inhibit the activity of S. aureus, while 50μg / mL is required to inhibit P. aeruginosa. This result is consistent with the mechanism of action of carbenicillin (Car), which is a β-lactam antibiotic that disrupts bacterial cell wall synthesis and causes structural defects by inhibiting mucopolysaccharide synthase. For P. aeruginosa, the partial impermeability of the outer membrane glycoprotein phospholipid bilayer to carbenicillin makes its permeability weak, so carbenicillin has a poor antibacterial effect against it.

[0096] Furthermore, the present invention uses equal amounts of free Met, Ga, Car, as well as GC and GCM, to conduct detailed bacterial activity inhibition studies. CCK-8 test results ( Fig. 9 A) showed that the Met treatment group had almost no effect on the survival rate of the two bacteria. In contrast, the Ga treatment group had no effect on the survival rate of S.aureus, but significantly reduced the survival rate of P.aeruginosa to 13.6%. This reduction may be due to the fact that Ga can interfere with iron uptake and interfere with iron signaling through the transcriptional regulator pvdS. The inhibitory effect of carbenicillin (Car) on S.aureus is stronger than that on P.aeruginosa. Whether it is GC or GCM treatment, the survival rate of S.aureus and P.aeruginosa can be reduced to about 95%, and there is no significant difference between the two. Furthermore, the present invention also evaluated the cell membrane permeability of S.aureus and P.aeruginosa after GCM nanoparticle treatment by double staining with SYTO9 and PI. SYTO9 can stain all bacterial DNA, while PI selectively stains bacterial DNA with damaged cell membranes, indicating cell death because PI cannot penetrate the intact cell membrane. Observations after treatment showed that the red fluorescence intensity of the GCM and GC treatment groups increased significantly ( Fig.10 ), indicating that the GCM group was significantly superior to the other groups in terms of antibacterial effect. The above results indicate that the antibacterial effect of GCM is exerted through the synergistic effect of Ga and carbenicillin (Car) release, rather than relying on Met, thereby effectively inhibiting bacterial proliferation. This finding was further confirmed by colony counts on agar plates ( Fig. 9 BC), confirming the strong antibacterial properties of GCM.

[0097] It can be seen that due to the presence of lipopolysaccharide and phosphopeptide in bacterial cell walls, their surfaces are usually negatively charged. Positively charged GCM can be "adsorbed" to the negatively charged surfaces of Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) through electrostatic attraction ( Figure 1 J). Subsequently, the pH-responsively released carbenicillin (Car) rapidly penetrated the bacterial cell wall and precisely inhibited further cleavage of peptidoglycan by transpeptidase, leading to bacterial lysis and death, a process also confirmed by the bacterial cell wall morphology observed by scanning electron microscopy (SEM) ( Figure 1 K). S. aureus and P. aeruginosa in the control group (i.e., untreated group) showed a relatively spherical and smooth morphology with intact cell walls. In the GC and GCM treated bacteria, however, the cell surface was observed to become wrinkled and cracked. These findings indicate that the bacterial wall was significantly damaged, significantly affecting the permeability of the bacteria. The released Ga 3+ ions enter the bacteria, interfere with the bacterial iron metabolism, and use the iron stress in the internal environment to inhibit bacterial growth. Finally, in the mildly acidic environment of bacterial infection, GCM can release drug-loaded substances through pH response, improve the utilization efficiency of antibiotics, and show synergistic antibacterial effects in vitro.

[0098] Synthesis and characterization of GCM-MN-CSH

[0099] The double-layer microneedle patch GCM-MN-CSH ( Figure 2 A) It consists of a drug delivery unit (GCM-MN) and an adhesive hydrogel patch (CSH). Figure 2 As shown in B, γ-polyglutamic acid (γ-PGA) with strong biocompatibility was selected as the matrix material of the GCM-MN needle tip to load GCM nanoparticles because of its strong mechanical properties after drying. PVP was selected as the backing layer material of GCM-MN because of its good biosafety, mechanical strength and rapid solubility. GCM-MN was prepared by a two-step template replication method, in which GCM nanoparticles were dispersed in water and mixed with γ-PGA. The mixture was filled into the needle tip of the needle mold by vacuum and low-speed centrifugation, and after removing the excess material, pure PVP pregel was added to form a GCM-MN microneedle array. For the CSH hydrogel patch, chitosan was first modified by covalently binding hydrogenated caffeic acid to form CSH. The formation of covalent bonds and the degree of binding were verified by Fourier transform infrared spectroscopy (FTIR) and ultraviolet spectroscopy (UV), as shown in Fig.11As shown. Subsequently, the CSH solution was cross-linked in the mold to prepare the hydrogel patch. Both GCM-MN and CSH components achieved 100% demolding rate, and the microneedles of GCM-MN were intact and evenly arranged in a 12×12 array ( Fig.12 ), CSH shows a consistent thickness ( Fig.13 ).

[0100] SEM images confirmed the pyramidal shape of the GCM-MN tips, with each needle being 640 μm long, 320 μm in base diameter, and 550 μm between the tips ( Figure 2 CD). The avascular epidermis, the outermost layer of the skin, is approximately 100 μm thick, while the underlying vascularized dermis is typically between 1000 and 2000 μm thick. Therefore, a 640 μm long GCM-MN is sufficient to penetrate the epidermis and reach the dermis. Fluorescence microscopy images of GCM labeled with rhodamine B show uniform red fluorescence at the needle tip ( Figure 2 E), indicating that the GCM is evenly distributed within the needle. Additional elemental maps ( Fig.14 ) further supports the uniform embedding of GCM, highlighting the successful preparation and use of GCM-MNs for transdermal drug delivery. The sharp pyramidal structure of GCM-MNs facilitates rapid and non-invasive insertion into the dermis. This was verified in tests conducted on porcine skin to evaluate the transdermal delivery potential of GCM-MNs. Figure 2 As shown in Figure F, after the microneedle penetrated the skin, the puncture channel stained with trypan blue could be clearly observed. In addition, the mechanical strength of GCM-MN was evaluated using an electronic tensile tester, and the results confirmed that the addition of GCM nanoparticles did not significantly impair the structural integrity of the microneedle (p>0.05). The test results showed that the mechanical strength of the microneedle was 0.52N / needle, which was sufficient to effectively pierce the skin without breaking. Fig.15 This is further confirmed.

[0101] Existing studies have shown that γ-polyglutamic acid (γ-PGA) and PVP, as biocompatible macromolecules, have good biodegradability and hygroscopicity. These properties enable GCM-MN to absorb skin interstitial fluid and degrade, thereby promoting the release of GCM nanoparticles. In order to evaluate the in vitro degradation of GCM-MN, it was placed in a sealed box at 100% relative humidity and the morphological changes were recorded. Within 15 minutes, the tip of the GCM-MN began to absorb water and dissolve, and it was completely dissolved after 75 minutes ( Figure 2 G). In vivo, when GCM-MNs were applied to the S. aureus-infected wounds of mice, the contact surface of the patch immediately became wet, indicating that the needle tips of the GCM-MNs had begun to dissolve ( Fig.17). Within 30 minutes, the GCM-MN in contact with the wound was almost completely dissolved. Compared with the dissolution process in the sealed box, the dissolution rate of the GCM-MN needle tip in the wound was faster, which may be due to the increase in the temperature of the wound skin, thereby promoting the acceleration of dissolution. In addition, the present invention also studied the release kinetics of GCM in PBS at pH 5.5 and 7.4. The release curve showed a sustained release pattern. After 2 hours, the cumulative release amounts under pH 5.5 and pH 7.4 conditions were 83.19±10.93μg / mL and 76.24±3.68μg / mL, respectively ( Figure 2 H). These findings highlight the hygroscopic and biodegradable properties of GCM-MNs and confirm their pH-responsive behavior, further underscoring their potential as an effective platform for rapid transdermal delivery of therapeutics.

[0102] The present invention also evaluated the adhesion properties of the CSH hydrogel patch to assess its suitability as a skin protective layer. The CSH hydrogel patch exhibited seamless skin adhesion and maintained contact even in flexed finger joints and under a 3-gram gravity pull, indicating that it has excellent adhesion stability and skin adaptability ( Figure 2 I and Fig.13 B). Further investigation focused on whether GCM-MNs affected the tissue adhesion properties of the CSH hydrogel patch. Freshly prepared CSH hydrogel patches and GCM-MN-CSH were attached to pig skin and vertically stretched until separation. The stress-displacement curves measured in the tensile adhesion test showed that the addition of GCM-MNs did not change the adhesion strength ( Figure 2 J). Therefore, GCM-MN-CSH exhibited strong adhesive properties and could effectively maintain attachment to skin tissue.

[0103] In vitro antibacterial activity of GCM-MN

[0104] Staphylococcus aureus (S. aureus) and Pseudomonas aeruginosa (P. aeruginosa) are widely present in chronic wounds, and the virulence factors and surface proteins they express can hinder wound healing. Staphylococcus aureus usually colonizes the surface layer of chronic wounds, while P. aeruginosa is common in deeper wounds. Wounds infected with these bacteria are larger and heal more slowly than uninfected wounds, which highlights the key role of microneedles (MNs) in targeting the surface and deep layers of wounds. In order to verify the in vitro antibacterial activity of GCM-MNs, the present invention tested the co-culture effects of blank microneedles (blank-MNs) and microneedles loaded with Met, Ga, Car, GC and GCM with Staphylococcus aureus and Pseudomonas aeruginosa in PBS. Figure 3As shown, after 3 hours of incubation, the cell viability of the GCM-MN and GC-MN groups was significantly reduced compared with the control group, blank microneedle group, and microneedle groups loaded with Met, Ga, and Car ( Figure 3 A) and the colony count decreased ( Figure 3 BC). It is noteworthy that the red fluorescence of the GCM-MN and GC-MN groups was significantly enhanced, indicating bacterial death ( Figure 3 D). This result is consistent with the antibacterial effect of GCM and GC nanoparticles, demonstrating that embedding GCM nanoparticles into microneedles can retain their antibacterial properties. Importantly, GCM-MNs exhibit antibacterial activity from the epidermis to the dermis, a property that is critical for accelerating wound healing.

[0105] In vitro biocompatibility assessment of GCM-MNs

[0106] Cytocompatibility and cell affinity are the key to the successful application of transdermal drug delivery systems. Understanding the interactions between nanoparticles (NPs) and microneedles (MNs) and cells, as well as their effects on cell growth and reproduction, is essential for evaluating their effects on biological tissues and ensuring the safety of in vivo applications, helping to prevent harmful effects that may inhibit wound healing or induce adverse reactions. The present invention used the CCK-8 method to evaluate the cytotoxicity of GCM nanoparticles and GCM-MNs at different concentrations on NIH / 3T3 fibroblasts and human umbilical vein endothelial cells (HUVECs). The results showed that even at high concentrations (100 μg / mL), after 1 day of co-culture, neither GCM nanoparticles nor GCM-MNs showed significant cytotoxicity, and cell viability remained above 95% ( Fig.17 and Figure 4 A), demonstrating its good cell compatibility. In addition, considering the inevitable contact with blood during in vivo application, it is also necessary to evaluate blood compatibility. The hemolysis rate of GCM nanoparticles and GCM-MNs was significantly lower than that of the positive control (water, inducing 100% hemolysis) and close to that of the negative control (normal saline). Even at a concentration of up to 100 μg / mL, the hemolysis rate was less than 2%, and no statistically significant differences were observed between the tested materials ( Figure 4 BC). These studies show that GCM nanoparticles and GCM-MNs do not cause adverse reactions in biological systems, confirming their safety in medical and biological applications. In summary, the GCM-MNs in the present invention exhibit excellent biocompatibility and have the potential to be used as a local transdermal delivery system for the treatment of infectious wounds.

[0107] 2.5. In vitro cell migration and angiogenesis characteristics of GCM-MNs

[0108] In the present invention, at a concentration of 100 μg / mL, GCM nanoparticles significantly increased the survival rate of HUVECs, reaching 118.8±5.5% ( Figure 4 A), indicating that it has a promoting effect on cell proliferation. This synergistic effect may be attributed to metformin (Met) in GCM nanoparticles. Studies have shown that Met downregulates autophagy of HUVECs by activating the Hedgehog signaling pathway, which is essential for tissue maintenance, renewal and regeneration. In addition, Met can also reduce oxidative stress, thereby further improving endothelial cell function. Subsequently, the present invention used an in vitro scratch experiment to evaluate the effects of GCM nanoparticles and GCM-MNs on cell migration. Semi-quantitative analysis showed that compared with the control group, fibroblasts and endothelial cells exposed to GCM nanoparticles and GCM-MNs migrated faster to the wound area after 24 hours and 12 hours of culture, respectively ( Fig.18 , Figure 4 DE). Specifically, the cell coverage of the wound gap in the GCM nanoparticles and GCM-MN groups was 38.3±0.3% and 42.9±3.9%, respectively, which was significantly higher than that in the control group (26.7±3.29%). It is worth noting that there was no significant difference between the GCM nanoparticles and GCM-MN groups (p>0.05). These results suggest that GCM nanoparticles and GCM-MNs can effectively promote the growth and migration of NIH / 3T3 fibroblasts and HUVECs, promote the rapid closure of the cell-free gap, and may accelerate the wound healing process.

[0109] Angiogenesis and vascular remodeling are crucial for tissue healing, as newly formed blood vessels provide nutrients and oxygen to wounds, accelerating wound closure. The present invention evaluated the angiogenesis potential of GCM nanoparticles (NPs) and GCM-MNs by in vitro angiogenesis assays. Figure 4 As shown in FH, HUVECs exposed to 50 μg / mL GCM nanoparticles and GCM-MNs showed significantly enhanced lumen formation, with more branch points and longer lumen length compared to the control group. This enhanced angiogenic effect is attributed to the Met in GCM nanoparticles and GCM-MNs through the activation of the AMPK signaling pathway and the upregulation of the RasGRP1-dependent VEGF signaling pathway, which are essential for the proliferation and migration of endothelial cells (confirmed by cell proliferation experiments). These signaling pathways help regulate angiogenesis and promote the formation of a strong vascular network, thereby promoting effective nutrient delivery and wound repair. Combined with the results of the HUVEC migration experiment, it can be seen that GCM-MNs exhibit the ability to promote cell migration and lumen formation, supporting its application in subsequent in vivo experiments.

[0110] 2.6. Healing effect of GCM-MN-CSH double-layer microneedle patch in bacterially infected wounds

[0111] To demonstrate the clinical potential of the microneedle patch of the present invention, the wound healing effect of the double-layer GCM-MN-CSH patch was evaluated in a female BALB / c mouse model infected with Staphylococcus aureus (S. aureus). Figure 5 A). First, GCM-MNs were applied directly to the wound under appropriate pressure to ensure that the microneedles could penetrate the skin, and then covered with a CSH hydrogel patch to maintain a moist healing environment, prevent dehydration, and protect the wound from secondary damage. Figure 5 As shown in BC, observations were performed on days 0, 2, 4, 6, and 8. By day 8, the wounds in the GCM-MN-CSH and GCM-MN groups were almost completely healed, with almost indistinguishable wound borders, compared with the blank microneedle (blank-MN), Met-MN, and GC-MN groups, which healed significantly slower, with scabs and depressions visible on the wound surface. The wounds in the control group remained moist and did not heal, with no scabs. Quantitative analysis by digital imaging ( Figure 5 D) shows that the relative wound area of ​​the GCM-MN-CSH and GCM-MN groups decreased to 26.10±7.79% and 40.65±16.31% on the 4th day, and further decreased to 9.53±2.72% and 14.39±8.65% on the 8th day, which was significantly better than the 47.43±17.02% of the control group (p<0.05). The complete removal of epidermal scabs in the GCM-MN-CSH and GCM-MN groups indicated the successful regeneration of epidermal tissue. Previous studies have shown that the application of antibacterial metal organic framework microneedles (MOF-MN) can accelerate the healing of wounds of similar size only after 12 days, while the GCM-MN-CSH in this study achieved this effect in only 8 days. This enhanced healing effect is attributed to the strong antibacterial effects of Ga and carbenicillin (Car), as well as the significant effects of Met on cell proliferation, migration and angiogenesis, which were confirmed by in vitro experiments.

[0112] 2.7. Antibacterial effect in vivo

[0113] On day 8, the antimicrobial effects of the different groups were evaluated in vivo by collecting skin tissues containing the entire wound area. Figure 5As shown in Figure EF, the results showed that the microneedles loaded with GC and GCM nanoparticles (GC-MN, GCM-MN, and GCM-MN-CSH) exhibited significant antibacterial effects, with a significant reduction in the bacterial load in the wound area. This confirmed the strong antibacterial potential of these carriers in vivo, consistent with their antibacterial effects in vitro. In particular, the GCM-MN-CSH group showed a very strong antibacterial effect, which was significantly superior to the GCM-MN group (p<0.05). This enhanced effect may be attributed to the CSH hydrogel patch, which not only maintains a moist healing environment but also protects the wound from external contamination, thereby further preventing additional damage and contamination of the wound.

[0114] 2.8. Systemic safety of the GCM-MN-CSH double-layer microneedle patch

[0115] In order to further evaluate the safety of the GCM-MN-CSH double-layer microneedle patch, the present invention conducted relevant biosafety tests in mice. Observations after treatment showed that there was no significant change in the weight of the mice, indicating that these treatments did not cause adverse effects on the whole body of the mice ( Figure 5 G). In addition, pathological analysis of the main organs of the mice (including heart, liver, spleen, lung and kidney) was performed by HE staining, and the results showed that there were no significant pathological abnormalities in these organs ( Fig.19 ). This further validates the safety of GCM-MN-CSH in vivo and suggests that it may be suitable for clinical application.

[0116] 2.9. Assessment of tissue regeneration, inflammation, and angiogenesis

[0117] To further evaluate the ability of GCM-MN-CSH double-layer microneedle patch to regenerate tissue after treatment, the present invention evaluated wound re-epithelialization and collagen production by histological analysis. HE staining evaluated wound contraction, epithelial clearance, granulation tissue formation, and tissue remodeling. Figure 6 As shown in A, the tissues of the control, blank-MN, Met-MN, and GC-MN groups showed obvious fractures and inflammatory cell infiltration, while the tissues of the GCM-MN and GCM-MN-CSH groups showed significantly reduced inflammatory cells, and the migration of epithelial tissue was significantly enhanced, resulting in a decrease in wound length and dermal gap. The thickness of the new epidermal tissue ( Figure 6 B), the results showed that the epidermal thickness of the GCM-MN-CSH group increased significantly and was significantly higher than that of the control group (p<0.0001). Masson trichrome staining was used to evaluate the production and deposition of collagen ( Figure 6A), both GCM-MN and GCM-MN-CSH groups showed better collagen arrangement and enhanced dark blue staining, indicating more intense collagen synthesis. Quantitative analysis showed that the collagen coverage of the GCM-MN-CSH group reached 66.15±4.40%, which was significantly better than that of the other groups ( Figure 6 C) These findings suggest that GCM-MN-CSH has a significant promoting effect in promoting collagen deposition and tissue remodeling.

[0118] 2.10. Immunohistochemical analysis of inflammatory response and angiogenesis

[0119] The inflammatory response caused by infection may hinder the healing process of the wound bed, among which macrophages play a vital role in wound healing and tissue regeneration. In the early stages of wound healing, M1 macrophages phagocytize necrotic / apoptotic neutrophils or damaged cells and produce proinflammatory cytokines (such as IL-1β and IL-6), which enhance the inflammatory response. In contrast, M2 macrophages produce anti-inflammatory cytokines and growth factors to help restore damaged tissues. To further study the inflammatory response, the present invention analyzed the expression levels of proinflammatory cytokines (IL-1β and IL-6) and markers of M1 (CD86) and M2 (CD206) macrophages by immunohistochemical staining ( Figure 6 A). The results showed that the expressions of IL-6 and CD86 in the control group, blank-MN group, Met-MN group and GC-MN group were significantly higher than those in the GCM-MN and GCM-MN-CSH groups ( Figure 6 DF), while the secretion of IL-1β in the control group and blank-MN group was significantly increased ( Figure 6 D). However, the GCM-MN and GCM-MN-CSH groups showed a significant decrease in IL-1β, IL-6, and CD86 levels, while the expression of CD206 increased significantly ( Figure 6 G). These results suggest that the reduced inflammatory response in the GCM-MN and GCM-MN-CSH groups facilitated the transformation of macrophages from the M1 to the M2 phenotype, thereby improving wound healing ability.

[0120] Angiogenesis is an important hallmark of healing because it promotes wound repair by providing oxygen, nutrients, and growth factors. The present invention evaluates new blood vessel formation by immunofluorescence staining to analyze mature angiogenesis, marking CD31 (red) on endothelial cells and α-SMA (green) on fibroblasts. Figure 6 A). GC-MN, GCM-MN and GCM-MN-CSH groups showed more mature vessel-like structures, indicating strong angiogenic ability ( Figure 6HI). In contrast, in the control, blank-MN, and Met-MN groups, there were fewer mature vessel-like structures. This difference may be due to the lack of antibacterial capacity in these groups, and persistent bacterial infection may have inhibited new angiogenesis at the wound site.

[0121] The above results show that wound healing was accelerated in the GCM-MN-CSH group, and this rapid recovery ability was attributed to the powerful antibacterial effect of the microneedle patch, the reduction of inflammatory response and the improvement of cell dynamics, including rapid proliferation and migration. In addition, the treatment promoted a high content of collagen fibers, the formation of granulation tissue and significant angiogenesis, all of which are important components for effective wound repair.

[0122] In summary, the multifunctional double-layer MOF-based microneedle patch (GCM-MN-CSH) in the present invention exhibits excellent antibacterial properties, promotes tissue regeneration, and has good biocompatibility in treating infected wounds. The microneedle array loads GCM nanoparticles into γ-PGA through rapid dissolution ability. The chitosan hydrogel layer modified by hydrogen salicylate provides good adhesion, and the double-layer microneedle patch has a regular morphology, uniform structure, and efficient percutaneous penetration ability. Antibacterial experiments confirmed that GCM-MN exerts a synergistic antibacterial effect by interfering with iron metabolism, and Ga 3+ and carbenicillin inhibit bacterial cell wall synthesis. In addition, it also enhances cell proliferation, migration and angiogenesis. In the S. aureus infected mouse wound model, the GCM-MN-CSH microneedle patch accelerated wound healing in a minimally invasive manner, showing a strong antibacterial effect, effective epithelialization process and granulation tissue formation. Mechanism analysis further revealed that the GCM-MN-CSH microneedle patch produced a significant therapeutic effect on infectious wounds by reducing the levels of inflammatory cytokines, promoting the polarization of M2 macrophages, enhancing collagen deposition and accelerating angiogenesis. Overall, the multifunctional properties of the GCM-MN-CSH double-layer microneedle patch in the present invention make it likely to become the preferred clinical application material for the treatment of infectious wounds.

Claims

1. A double-layer microneedle patch, characterized in that: It includes a drug delivery unit and an adhesion unit, wherein the drug delivery unit is a GCM-MN microneedle array, and the adhesion unit is a CSH hydrogel patch. Furthermore, when in use, the GCM-MN microneedle array is first applied to the wound site by pressure to ensure that the microneedles can penetrate the skin at the wound site, and then the CSH hydrogel patch is covered on the GCM-MN microneedle array to ensure a moist healing environment.

2. The double-layer microneedle patch according to claim 1, characterized in that: The GCM-MN microneedle array uses γ-PGA as the matrix material of the needle tip and PVP as the backing layer material.

3. The double-layer microneedle patch according to claim 1, characterized in that: The needle tips of the GCM-MN microneedle array are all pyramid-shaped, and the length of each needle tip is 640 μm, the base diameter is 320 μm, and the distance between adjacent needle tips is 550 μm.

4. A method for preparing a double-layer microneedle patch as claimed in claim 1, 2 or 3, characterized in that The following steps are involved: (1) Synthesis of GCM; (2) Preparation of GCM-MN microneedle arrays; (3) Preparation of CSH hydrogel patch.

5. The method for preparing a double-layer microneedle patch according to claim 4, characterized in that: The synthesis steps of GCM in step (1) are as follows: Ga(NO3)3 and Met are mixed in water to react and produce Ga 3+ and Met coordination complex; subsequently, carbenicillin solution was added to 3+ A Ga-Car-MOF complex is formed; after stirring the reaction, the precipitate is collected and washed to remove unreacted substances; finally, white GCM nanoparticles are obtained after freeze-drying.

6. The method for preparing a double-layer microneedle patch according to claim 4, characterized in that: The preparation steps of the GCM-MN microneedle array in step (2) are as follows: a two-step template replication method is used. First, the GCM nanoparticles prepared in step (1) are dispersed in water and mixed with γ-PGA, and the mixture is obtained by vacuum and low-speed centrifugation; then, the mixture is filled into the needle tip of the needle mold, and after removing excess material, pure PVP pregel is added to form a GCM-MN microneedle array.

7. The method for preparing a double-layer microneedle patch according to claim 4, characterized in that: The preparation steps of the CSH hydrogel patch in step (3) are as follows: first, chitosan is modified by covalently bonding hydrogenated caffeic acid to form CSH powder; then, the CSH solution is cross-linked in a mold to prepare a CSH hydrogel patch.

8. An application of the double-layer microneedle patch as claimed in claim 1, 2 or 3, characterized in that: Application of the double-layer microneedle patch in the preparation of infectious wound healing medical devices.

Citation Information

Patent Citations

  • Nano-reactor hydrogel for promoting healing of diabetic wounds as well as preparation method and application of nano-reactor hydrogel

    CN118079075A

  • Cu-MOF-based composite antibacterial hydrogel wound dressing and preparation method thereof

    CN118873734A

  • Microacupuncture needle paster for improving skin hyperplastic scars and preparation method of microacupuncture needle paster

    CN110935097A

  • Preparation method and application of photosensitizer Ga-MOF antibacterial particles

    CN116585469A

  • Metformin and CeO2 assembled ROS response type hydrogel microneedle and application thereof in diabetes wound treatment

    CN118846117A

Cited By

  • Application of metformin in preparation of skin anti-photoaging drugs or medical instruments

    CN120189400A